PERKEMBANGAN KAJIAN KOMUNIKASI PEMASARAN DI KOTA MALANG : SEBUAH META ANALISIS - Rezki Rahmawati; Antoni Antoni; Bambang Dwi Prasetyo (Universitas Merdeka Malang, 2019)
AbstractThis research is a meta-analysis of the development of the study of marketing communication undergraduate thesis in Malang during 2014-2018. This research aims to find out how the development of marketing communication studies with the philosophy of science approach in order to provide references for mapping marketing communication studies. The undergraduate thesis researched in this research is 229 theses from three different universities with a focus on the use of theory in marketing communication theses. The results of the research show that the most widely used communication theory in marketing communication thesis is the Elaboration Likelihood Model (ELM) theory. The interesting thing found in this research is the more use of marketing concepts and theories than the use of communication theory in undergraduate thesis with the theme of marketing communication. Keywords: marketing communication, meta-analysis, philosophy of scienceDOI : https://doi.org/10.26905/nomosleca.v5i1.2782